2015
DOI: 10.1371/journal.pone.0134716
|View full text |Cite
|
Sign up to set email alerts
|

Shame and Guilt-Proneness in Adolescents: Gene-Environment Interactions

Abstract: Rooted in people’s preoccupation with how they are perceived and evaluated, shame and guilt are self-conscious emotions that play adaptive roles in social behavior, but can also contribute to psychopathology when dysregulated. Shame and guilt-proneness develop during childhood and adolescence, and are influenced by genetic and environmental factors that are little known to date. This study investigated the effects of early traumatic events and functional polymorphisms in the brain-derived neurotrophic factor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 96 publications
1
10
1
2
Order By: Relevance
“…These data corroborate the important role that external shame plays in several mental health problems (Gilbert, 2009(Gilbert, , 2010. This may be particularly true for adolescents who crave for social acceptance and are, thus, more vulnerable to socially shameful experiences (Gilbert & Irons, 2009;Szentágotai-Tătar et al, 2015). Such shameful experiences and shame feelings can play a key role in RUNNING HEAD: External shame across diverse samples of adolescents 6 youth psychosocial maladjustment and mental health outcomes (Cunha et al, 2012;Gilbert & Irons, 2009).…”
supporting
confidence: 58%
“…These data corroborate the important role that external shame plays in several mental health problems (Gilbert, 2009(Gilbert, , 2010. This may be particularly true for adolescents who crave for social acceptance and are, thus, more vulnerable to socially shameful experiences (Gilbert & Irons, 2009;Szentágotai-Tătar et al, 2015). Such shameful experiences and shame feelings can play a key role in RUNNING HEAD: External shame across diverse samples of adolescents 6 youth psychosocial maladjustment and mental health outcomes (Cunha et al, 2012;Gilbert & Irons, 2009).…”
supporting
confidence: 58%
“…This finding is not consistent with studies that found that the low-functioning BDNF Met66 allele and CM/childhood trauma or early life adversity or stress interact to predict increased susceptibility for psychopathology, including anxiety-related temperamental traits, such as neuroticism (Gatt et al, 2009) and guilt-proneness (Szentágotai-Tətar et al, 2015), anxiety symptoms (Gatt et al, 2009) and mood disorders and associated symptoms (Aguilera et al, 2009; Carver et al, 2011; Gutiérrez et al, 2015). Our findings are also not in agreement with G x E studies that found an interactive effect of the higher functioning Val66 allele and environmental exposures (i.e.…”
Section: Discussioncontrasting
confidence: 61%
“…Similarly, a recent longitudinal study has reported that harsh parenting in childhood is related to increased shame-proneness, but not guilt-proneness in adolescence [28]. Other childhood traumatic events such as parental conflict and sexual abuse were not associated with proneness to shame and guilt [28, 29]. Another recent study showed that shame-proneness may be increased in adolescents with a history of serious illness or injury [29].…”
Section: Introductionmentioning
confidence: 99%
“…Other childhood traumatic events such as parental conflict and sexual abuse were not associated with proneness to shame and guilt [28, 29]. Another recent study showed that shame-proneness may be increased in adolescents with a history of serious illness or injury [29]. Research focusing on situational shame and guilt has also documented their relation to childhood trauma.…”
Section: Introductionmentioning
confidence: 99%